Characterization of the teaching aids in the teaching-learning process in Physical Education - César Perazas Zamora; Yoannis Gil López; Yadiel Pardo García; Luis Orlando Soler Cruz (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2017)
The aids and resources of teaching are an important didactic component inside of the teaching learning process, they are the material support of the teaching aids, its adequate use warrant the quality of the process. With the accelerated development of the science, technique and technologies the audiovisual aids has passed to form part of the teaching learning process humanizing the teacher's work and favouring the transmission of knowledge with a truly scientific approach. The objective of this article is standing out the main concepts, definitions and advantages of the teaching aids more used nowadays, its importance as didactic component and its adequate use in the teaching learning process linked with the objective, method and content, ensuring the lasting learning that contributes to raise the integral general culture of the students. Besides it deals with the topic of audiovisual aids as one of the components of the teaching learning process, it is offered concepts and definitions from different authors and emphasized the advantages, use and importance of its systematic and planned use.